Edukasi Fisioterapi Mengenai Osteoarthritis dengan Memberikan Latihan Strengthening pada Lansia di Posyandu Sawojajar Kota Malang - Renita Risky Parvianti; Safun Rahmanto; Wida Sekarani Paramita (Lembaga Pengembangan Kinerja Dosen, 2025)
Osteoarthritis (OA) is one of the most common degenerative diseases of the joints experienced by the elderly, characterized by damage to cartilage that causes pain, stiffness, and decreased joint function. This disease usually occurs in joints that support body weight, such as the knees, which can interfere with the mobility and quality of life of the elderly. To overcome this, one approach that can be done is physiotherapy, which focuses on strengthening exercises to improve joint stability and function. Exercises such as straight leg raise, heel raise, and wall squat can help strengthen the muscles around the knee joint, reduce pain, and improve mobility in the elderly. This physiotherapy counseling was carried out at the Sawojajar Posyandu on October 20-24, 2024, with the aim of educating the elderly about Osteoarthritis and providing strengthening exercises. During the activity, pre-tests and post-tests were carried out to measure the effectiveness of the counseling. The results of the evaluation showed an increase in the elderly's knowledge about OA and their ability to perform the strengthening exercises that had been taught. The education delivered using leaflets also helps the elderly better understand ways to prevent and manage OA with proper physical exercise. In conclusion, this activity succeeded in improving the knowledge and skills of the elderly in dealing with Osteoarthritis through structured and easy-to-understand physiotherapy interventions.